Achieving a Cure Without Total Mesorectal Excision in Rectal Adenocarcinoma. Issue 2 (4th November 2022) - Hall, William A.; Smith, J. Joshua
Abstract : The Oncology Grand Rounds series is designed to place original reports published in the Journal into clinical context. A case presentation is followed by a description of diagnostic and management challenges, a review of the relevant literature, and a summary of the authors' suggested management approaches. The goal of this series is to help readers better understand how to apply the results of key studies, including those published in Journal of Clinical Oncology, to patients seen in their own clinical practice. Rectal cancer is a curable disease, yet curing the disease can be associated with lifelong morbidity because of the nature of the curative-intent treatment strategies. A major focus of modern prospective trials has been to maintain current cure rates, while minimizing lifelong lifestyle alterations and maximizing quality of life. Navigating the complex landscape of therapeutic options for rectal adenocarcinoma with a focus to accomplish this quality-of-life improvement is a critical focus area for future clinical trials. Many challenges remain on the path to optimizing cure and minimizing morbidity, and include improving initial staging accuracy, more precise selection of neoadjuvant therapy used for each patient, choosing the optimal surgical management strategy, and ensuring modern radiation therapy approaches are being used. Finally, organ preservation strategies have moved to the forefront in the management of both early and locally advanced rectal cancers and hold the potential for significant changes to come for patients with rectal cancer. Herein, we highlight some of the challenges remaining in the field, progress made, and how the recent data from the Canadian Cancer Trials Group phase II trial can be put into context with the ACOSOG Z6041, CARTS, and GRECCAR2 trials.